Islam, Modernity, and the Liminal Space Between. - Meehan, Mark W. (Newcastle upon Tyne : Cambridge Scholars Publishing, 2013)
This book investigates the development and function of the Institute of Traditional Islamic Art and Architecture (ITIAA) in Amman, Jordan. A vertical case study using grounded theory methodology, the research creates a rich and holistic understanding of the Institute. Specific areas of study include the factors involved in the founding of the Institute within the context of Arab and Jordanian higher education, the role of traditional Islamic philosophy in the function of the Institute, and th ...
Traditional Islamic Philosophy and the Institute'sCurriculumTraditional Islamic Pholosophy and the Students of the Institute ; Student Survey Responses; Student Interview Responses; Conclusions; CHAPTER SIX; General Understanding ; The Role; The Function of Communitas; Value Synthesis; Products of Liminality and their Anticipated Rolein Jordan; The Pervasive Role of Beauty; Conclusions; CHAPTER SEVEN; Research Summary; Implications of the Study; Reflection on Method and Results; Funding as a Definitive Aspect of the Research Process; Potential Further Research; WORKS CITED.
Print version record.
Includes bibliographical references.
English.
Master record variable field(s) change: 072
Keywords: Education, Higher -- Jordan; Islamic education -- Philosophy; RELIGION -- Biblical Studies -- New Testament; Education, Higher; Islamic education -- Philosophy; Jordan; Islam -- 19th century; Islam -- 20th century; Islamic modernism; Religion; Electronic books; Electronic books